Pengaruh Motivasi terhadap Minat Menabung di Bank Syariah - Siti Fatimah; Siti Zariah (STAI Auliaurrasyidin Tembilahan, 2022)
This research is motivated by the lack of interest of Islamic economics students at STAI Auliaurrasyidin Tembilahan in using Islamic banking products, even though as students who are engaged in Islamic economics, of course, they already know and understand Islamic banking, they should be able to contribute in helping the development of Islamic banking. This study aims to determine the significant effect of motivation on student interest in saving in Islamic banks. In this study, the research subjects were students of the Islamic Economics Study Program STAI Auliaurrasyidin Tembilahan class of 2017-2019, while the object of the research was the influence of motivation on student interest in saving in Islamic banks. This type of research is quantitative research because the data obtained are a collection of numbers. The population in this study amounted to 180 students. To determine the sample used probability sampling technique with simple random sampling method and using the formula Isaac and Michael, obtained a total sample of 123 students. Data analysis used a simple regression method with the help of the SPSS (Statistical Product and Service Solution) 23.0 for windows program. It can be concluded that motivation has a positive and significant effect on the interest of Islamic economics students at STAI Auliaurrasyidin Tembilahan.